Implementation of Storytelling in Instilling Character Education Values in Early Childhood at Mentari Preschool Jakarta - Alwahdy, Dina Faisal; Binar, Whenty; Hardiyati, Pauli; Sefiliani, Fiskha Nur; Susilawati, Susilawati (JEdu: Journal of English Education, 2024)
Storytelling is one of the activities that can be done in class because it has many benefits, especially for young children. As a teacher and parent, reading stories through Storytelling is very necessary to increase closeness with children and can also instill the value of character education in early childhood. Based on the results of this research, researchers are interested in conducting similar research with the same variables, but with different samples, locations and student backgrounds. The research was conducted on early childhood students at Mentari Preschool Jakarta where these students had upper middle class family backgrounds and wider access to English-speaking information, environment and culture. This research is qualitative research using the classroom action method through 2 cycles. Sampling method with 20 K1B class students. The research was taken based on the Rancangan Pembelajaran Harian (RPPH) with fixed activities on moral values and character. The research results show that Storytelling activities can increase students' educational and moral values.